A Retrospective Case Report on the Longevity of a Reimplanted Closed-Apex Avulsed Canine. (13th February 2020) - Leow, Julian; Amanullah, Robin
Abstract : For an avulsed tooth with closed apices, it is recommended that the tooth undergoes elective root canal treatment. We however present in this case report a 73-year-old Afro-Caribbean lady, with an asymptomatic, untreated, self-replanted lower left canine which suffered an avulsion 45 years ago. The patient reported no loss of function. This case illustrates the potentially positive outcome of a replanted, non-root-treated, avulsed closed-apex tooth while highlighting the significance of patient-related factors.